Sustainable Development Goals (SDGs) applied to Mechanical Engineering - Carlos Llopis-Albert; Francisco Rubio; Shouzhen Zeng; Juan Grima-Olmedo; Carlos Grima-Olmedo (Multidisciplinary Journal for Education, Social and Technological Sciences, 2022)
In 2015, the United Nations approved the 2030 Agenda on Sustainable Development, an opportunity for countries and their societies to face the challenge of successfully addressing the transition to a more sustainable future for people and the planet, leaving no one behind. The agenda defines a total of 17 Sustainable Development Goals (SDGs) of universal application to promote economic growth, a commitment to social needs and the protection of the environment. For the successful achievement the ambitious and demanding SDGs, individuals, businesses, governments, and higher education institutions should work collaboratively.